The Role of the Energy Sector in the Command and Control Function of Cities in Conditions of Sustainability Transitions - Piotr Raźniak (MDPI AG, 2021)
The largest companies that are part of the energy sector are defined by Forbes as those associated with the production of energy from nonrenewable sources and they play a very significant role in the world economy and in the generation of the command and control (C & C) function of cities. No comprehensive studies are available at the present time illustrating changes in financial performance in relation to the share of the largest firms in the energy sector in terms of their role in the generation of the C & C function. Thus, the aim of the paper is to show changes in financial performance and the impacts of energy sector companies on the C & C function of cities as well as to show spatial variances in the sector’s geography. The energy sector is developing most rapidly in Chinese cities, although it does not play a major role in the most important cities in the world via its impact on the C & C function—this may be due to rapid growth in other sectors of the economy. It is, however, very important in smaller cities. On the other hand, a large share of the energy sector involved in the development of renewable sources of energy may disturb the position of cities whose C & C function relies on energy sector companies. Thus, forecasts are needed for the sector and its impact on the command and control function of cities for the period of transition from nonrenewable sources to renewable ones. One new area of research is the formulation of methods that would allow the determination of the effects of economic recessions in the future on the financial health and C & C function impacts of the energy sector.